On having a Mind, having a Body, and being a Person - Hacker, Peter Michael Stephan (Вестник Томского государственного университета. Философия. Социология. Политология)
The basic ideas of P.M.S. Hacher’s writings are considered in the Introduction. The main subject of the considerations is Philosophy of the Human Being. The article of P.M.S. Hacker that is presented in English is devoted to the subject.